The Role of Fatty Acid Metabolites in Vaginal Health and Disease: Application to Candidiasis - Baldewijns, Silke; Sillen, Mart; Palmans, Ilse; Vandecruys, Paul; Van Dijck, Patrick; Demuyser, Liesbeth (Frontiers in Microbiology, 2021)
Although the vast majority of women encounters at least one vaginal infection during their life, the amount of microbiome-related research performed in this area lags behind compared to alternative niches such as the intestinal tract. As a result, effective means of diagnosis and treatment, especially of recurrent infections, are limited. The role of the metabolome in vaginal health is largely elusive. It has been shown that lactate produced by the numerous lactobacilli present promotes health by limiting the chance of infection. Short chain fatty acids have been mainly linked to dysbiosis, although the causality of this relationship is still under debate. In this review, we aim to bring together information on the role of the vaginal metabolome and microbiome in infections caused by Candida. Vulvovaginal candidiasis affects near to 70% of all women at least once in their life with a significant proportion of women suffering from the recurrent variant. We assess the role of fatty acid metabolites, mainly short chain fatty acids and lactate, in onset of infection and virulence of the fungal pathogen. In addition, we pinpoint where lack of research limits our understanding of the molecular processes involved and restricts the possibility of developing novel treatment strategies.